Health promotion and cardiovascular risk reduction in people with spinal cord injury: physical activity, healthy diet and maintenance after discharge— protocol for a prospective national cohort study and a preintervention- postintervention study - Nicolaj Jersild Holm; Tom Møller; Lis Adamsen; Line Trine Dalsgaard; Fin Biering-Sorensen; Lone Helle Schou (BMJ Open)
Introduction Spinal cord injury (SCI) predisposes those who suffer from it to physical inactivity and weight gain; consequently, death due to cardiovascular diseases is more frequent among people with SCI than in the general population. The literature documents a consensus about an interdisciplinary multimodal approach for the prevention and treatment of cardiovascular risk factors including overweight and obesity in people with SCI, focusing on diet, physical activity (PA) and behavioural interventions. This study will investigate implementation of recommendations from a recent clinical practice guideline for identification and management of cardiometabolic risk after SCI through multimodal patient education in a subacute clinical setting.Methods and analysis All patients who are aged 18 years or older with an SCI within the previous 12 months and admitted to highly specialised rehabilitation are included, regardless of SCI aetiology or neurological level. A primary study designed as a controlled, pragmatic, preintervention- postintervention study with 6-month follow-up evaluates the effect of the clinical intervention; a prospective national cohort study on body mass index (BMI) serves as a historical control. The intervention consists of a standardised approach to patient education about cardiovascular risk factors, PA and a healthy diet that begins at the outset of primary SCI rehabilitation and is integrated into existing settings and workflows. Outcome measures are collected at admission, discharge and 6 months after discharge and include peak oxygen uptake (VO2peak) (primary outcome), BMI, body composition, metabolic profile, neurological status, level of functioning, depression, quality of life, objective PA (accelerometry), self-reported PA, self-assessed PA ability, shared decision making, and dietary habits. Test–retest reliability of four VO2peak test protocols are investigated, as is test–retest reliability of a multisensor accelerometer in a rehabilitation setting.Ethics and dissemination The project is approved by the Committees on Health Research Ethics in the Capital Region of Denmark on 10 July 2018 (Journal-nr.: H-18018325). The principal investigator obtains informed consent from all participants. The interventions in the project are closely related to existing rehabilitation care, and the risk of pain and discomfort is considered modest. Any unintended events related to the elements of the intervention are reported, according to existing regional procedures. Data are stored in a secure web-based database (Redcap). The primary study and prospective cohort study are registered at Clinicaltrials.gov. Positive and negative results will be submitted to relevant scientific journals related to SCI for publication. Important protocol modifications are reported to the Committees on Health Research Ethics in the Capital Region of Denmark.Trial registration numbers NCT03689023 and NCT03369080.